Heat Transfer Model of Pneumatic End-Position Cylinder Cushioning - Nazarov, Fedor; Weber, Jürgen (International Journal of Fluid Power, 2021)
In this paper a thermal model of a pneumatic cylinder with an integrated pneumatic end cushioning is presented. Being a part of a multidomain model presented in former research, this model is needed to simulate and analyse the thermodynamic processes in the pneumatic end cushioning and to elaborate a novel design strategy for damping systems with a higher capability on kinetic energy absorption and robust performance under fluctuating operating conditions. For this purpose, a proper heat exchange model is inevitable to calculate the pressure in the cushioning volume and consequently the deceleration of the load. An approach of splitting the complex geometry of cylinder into simple geometries, such as plain or cylindrical surfaces, is used in this study for a fast computation of convective heat flow rates. To validate this approach, the simulation results were compared with the measurements, carried out at different supply pressures, piston speeds and end cushioning throttle openings. The model will be used further for sensitivity analysis and robust optimisation of the cushioning system design.